A new discrete fracture approach based on the use of coupling finite elements for modeling fluid transport in naturally fractured porous media - Manzoli, Osvaldo L. [UNESP]; Borges, Livia F.A.; Rodrigues, Eduardo A. [UNESP]; Cleto, Pedro R. [UNESP]; Maedo, Michael A. [UNESP]; Bitencourt, Luís A.G. (Elsevier, 2021)
The presence of natural fractures in a porous medium strongly influences the fluid flow path. The complex geometric characteristics of the fracture network create preferential channels that change the permeability of the medium. In this context, this paper presents a novel discrete fracture model to address the hydrodynamic behavior of naturally fractured porous media by using a coupling scheme in which the initially independent standard finite element meshes of porous rock and fractures are coupled via coupling finite elements to enforce the continuity of the pressure field between the meshes through a penalty parameter. The main feature of the technique is the capacity to treat problems with non-matching, overlapping and interfacial meshes with no need to add extra degrees of freedom to describe the compatibility between the meshes. In addition, the proposed coupling finite elements also connect non-conforming meshes of fractures, so that their interaction emerges naturally from the coupling scheme. The new theoretical framework and finite element equations are described in detail and 2D and 3D numerical experiments are conducted to validate and verify the technique against results reported in the literature. The obtained results show that the proposed coupling scheme is efficient and able to capture the main phenomena associated with the fluid transport in fractured porous media.
Keywords: Coupling finite element; Embedded discrete fractures; Fluid flow; Naturally fractured reservoirs; Non-matching meshes